3d metal complexes in T-shaped geometry as a gateway to metalloradical reactivity - Ott, Jonas C.; Bürgy, David; Guan, Hairong; Gade, Lutz H. (Accounts of chemical research, 2022)
ConspectusLow-valent, low-coordinate 3d metal complexes represent a class of extraordinarily reactive compounds that can act as reagents and catalysts for challenging bond-activation reactions. The pursuit of these electron-deficient metal complexes in low oxidation states demands ancillary ligands capable of providing not only energetic stabilization but also sufficiently high steric bulk at the metal center. From this perspective, pincer ligands are particularly advantageous, as their prearranged, meridional coordination mode scaffolds the active center while the substituents of the peripheral donor atoms provide effective steric shielding for the coordination sphere. In a T-shaped geometry, the transition metal complexes possess a precisely defined vacant coordination site, which, combined with the often observed high-spin electron configuration, exhibits unusually high selectivity of these compounds with respect to one-electron redox chemistry. In light of the intractable reaction pathways typically observed with related electronically unsaturated 3d transition metal complexes, the pincer coordination mode enables the isolation of low-valent compounds with more controlled and unique reactivity. We have thus investigated a series of T-shaped metal(I) complexes using three different types of pincer ligands, which may be regarded as “metalloradicals” due to their selectively exposed unpaired electrons.These compounds display remarkably high thermal stability and represent rarely observed “naked” monovalent metal species featuring both monomeric and dimeric structures. Extensive reactivity studies using various organic substrates highlight a strong tendency of these paramagnetic compounds to undergo one-electron oxidation, leading to the isolation of a plethora of metal(II) species with reduced organic ligands as unusual structural elements. The exploration of C2 symmetric T-shaped Ni(I) complexes as asymmetric catalysts also shows success in enantioselective hydrodehalogenation of geminal dihalogenides. In addition, this specific class of low-valent, low-coordinate complexes can be further diversified by introducing redox-active pincer ligands or building homobimetallic systems with two T-shaped units.This Account focuses on the discussion of selected examples of iron, cobalt, and nickel pincer complexes bearing a [P,N,P] or [N,N,N] donor set; however, their electronic structure and radical-type reactivity can be broadly extended to other pincer systems. The availability of various types of pincer ligands should allow fine-tuning of the reactivity of the T-shaped complexes. Given the unprecedented reactivity observed with these compounds, we expect the studies of T-shaped 3d metal complexes to be a fertile field for advancing base metal catalysis.
Gesehen am 01.09.2022